2005
DOI: 10.1002/app.21628
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and structural properties of poly(vinyl alcohol) doped with hydroxypropyl cellulose

Abstract: ABSTRACT:The growth and importance of medical and related health care and hygiene textile sectors are attributed to the improvement and innovations in both textile technology and medical procedures. The aim of this study was to examine some of the structural properties of pure poly(vinyl alcohol) (PVA) and hydroxypropyl cellulose (HPC) doped PVA of different weight percentages. This will lead to the choice of the optimum conditions suited for specific medical and surgical applications for which textile materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 31 publications
1
37
0
Order By: Relevance
“…This polymer is used in adhesives, cosmetics, textile and pharmaceutical industry, paints, and even as a colloid protector in emulsion polymerization 1. Numerous advantageous properties of PVA have lead to its broad practical applications due to its chemical resistance, favorable physical properties, and complete biodegradability 2. Furthermore, it is water soluble and has broad industrial application as a result of its high capability of water absorption 3…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This polymer is used in adhesives, cosmetics, textile and pharmaceutical industry, paints, and even as a colloid protector in emulsion polymerization 1. Numerous advantageous properties of PVA have lead to its broad practical applications due to its chemical resistance, favorable physical properties, and complete biodegradability 2. Furthermore, it is water soluble and has broad industrial application as a result of its high capability of water absorption 3…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, highly hydrolyzed PVA shows a better thermal stability than PVA with a low degree of hydrolysis 6. Degradation of PVA bulk material has been studied by several authors,1, 2, 5, 6 and it was concluded that the elimination of hydroxyl side groups is present and considerable amounts of isolated and conjugated polyenes in the degradation residue and small amounts of carbonyl groups could appear. Moreover, Ultraviolet–visible (UV–vis) spectroscopy has shown that the unsaturated double bonds produced by elimination do not lead to the formation of noticeable amounts of conjugation 5…”
Section: Introductionmentioning
confidence: 99%
“…[18] However, polyvinylalcohol (PVA), the polymer most widely used so far [3][4][5][6][7][8] for this application, does not meet these requirements, presenting high loss in the telecommunications wavelength range ($1550 nm), as discussed below. Moreover, it has a low glass-transition temperature (T g $ 85 8C), decomposes in air just above 200 8C, [20,21] and absorbs large amounts of moisture due to the high concentration of -OH groups along its chain. [21] Cellulose derivatives have also been used as polymer matrices for SWNTs, [11] though their hydrophilic character [21] may affect their transparency on a long-term basis due to moisture absorption.…”
mentioning
confidence: 99%
“…The XRD pattern of the HPC/graphene composites by the casting method is included in Figure 4b. Once graphene had been compounded into HPC by both methods, the relatively increased ratio of the intensity at 19.5° compared with that at 8.2° indicates that their crystallinities were all increased with increasing loading of graphene 43. The heterogeneous‐nucleation effect that was induced by graphene44 may be responsible for the facilitated crystallization of the HPC chains in the HPC/RGO composites.…”
Section: Resultsmentioning
confidence: 99%